(untitled) (Global Journal of Medical Research, 2023)
A 14-year-old female presented with multiple dark coloured, itchy lesions on legssince5 months. On examination, multiple violaceous papules to plaques of varying sizes (1cm - 5cm) were present on the extensor aspects of legs, forearm and dorsum of feet bilaterally. (Figs 1-3).Skin biopsy from the lesion showed hyperkeratosis, hypergranulosis, vacuolar degeneration of basal layer, band of dense lymphocytic inflammatory infiltrate in the papillary dermis, with perivascular histiocytic infiltrate confirming the diagnosis of lichen planus (LP) (Fig 4,5). She was started on topical corticosteroids, antihistamines and emollients. After 3 months patient had aggravation of LP with patchy hair loss over the scalp. On examination multiple, smooth alopecic patches of varying sizes, the largest being 4 x 3 cm, were noticed on the scalp. She was diagnosed clinically as alopecia areata (AA) (Fig 6). Investigations like complete blood count, liver function test, thyroid profile, anti-nuclear antibody, rheumatoid arthritis factor, C-reactive protein, ESR, VDRL, HBV, HCV, urine microscopy were normal. In view of progressing lesions of LP and AA, she was started on oral mini pulse therapy-betamethasone 5 mg twice weekly and was advised for follow – up. Good response was noticed by four weeks with resolution of LP and regrowth of hair over few patches.